2018
DOI: 10.1126/scitranslmed.aar3752
|View full text |Cite
|
Sign up to set email alerts
|

Striatal dopamine regulates systemic glucose metabolism in humans and mice

Abstract: The brain is emerging as an important regulator of systemic glucose metabolism. Accumulating data from animal and observational human studies suggest that striatal dopamine signaling plays a role in glucose regulation, but direct evidence in humans is currently lacking. We present a series of experiments supporting the regulation of peripheral glucose metabolism by striatal dopamine signaling. First, we present the case of a diabetes patient who displayed strongly reduced insulin requirements after treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 80 publications
4
65
0
Order By: Relevance
“…The circadian‐timed administration of either dopamine agonist systemically or dopamine to the SCN clock area in insulin‐resistant animals to induce (mimic) the normal circadian peak of dopaminergic activity at the SCN pacemaker that is diminished in insulin resistance states has been observed to reduce chronic overactivity of SNS pre‐autonomic neurons in the hypothalamus and measures of subsequent chronic activation of peripheral sympathetic tone in insulin‐resistant states . Moreover, reduction of brain dopamine synthesis in healthy humans for just a couple of days induces peripheral insulin resistance …”
Section: Introductionmentioning
confidence: 99%
“…The circadian‐timed administration of either dopamine agonist systemically or dopamine to the SCN clock area in insulin‐resistant animals to induce (mimic) the normal circadian peak of dopaminergic activity at the SCN pacemaker that is diminished in insulin resistance states has been observed to reduce chronic overactivity of SNS pre‐autonomic neurons in the hypothalamus and measures of subsequent chronic activation of peripheral sympathetic tone in insulin‐resistant states . Moreover, reduction of brain dopamine synthesis in healthy humans for just a couple of days induces peripheral insulin resistance …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Diepenbroek et al showed that DBS of the nucleus accumbens shell could produce changes in peripheral glucose metabolism [54]. Both human ventral striatal DBS in a patient with obsessive compulsive disorder and optogenetic activation of dopamine D1 receptor neurons in nucleus accumbens of mice have been shown to increase glucose tolerance and insulin sensitivity [55]. Manipulation of lateral hypothalamic neuronal populations are known to alter both basal metabolic rate and spontaneous physical activity [56] and could be possible mediators of our DREADD manipulation by altering energy homeostatic processes that produced the observed weight changes.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with our finding of genetic sharing between T2D as well as HbA1c levels and ‘aggressive taboo thoughts’. In addition, a recent study demonstrated that bilateral deep brain stimulation (DBS), a safe and effective treatment option for pharmaco-resistant OCD, not only reduced OCD symptoms but also decreased fasting insulin levels in the blood of both OCD patients with T2D and non-diabetic OCD patients (47). Moreover, insulin in the CNS - either entering from the periphery by crossing the blood brain barrier (48) or synthesized in the CNS (49) - has important non-metabolic functions, including modulating synaptic plasticity (50) and learning and memory (51, 52).…”
Section: Discussionmentioning
confidence: 99%